Innovation of functional cookies for substitution of soybean flour (Glycine max), chicken liver and purple sweet potato (Ipomoea batatas L.) for pregnant women with anemia - Inggi Arulia Yoso; Astrid Noviana (AcTion: Aceh Nutrition Journal, 2026)
Iron deficiency anemia remains a health problem among pregnant women, with a prevalence of 27.7% in Indonesia. Consuming iron-and vitamin C can help prevent anemia. This study aimed to develop cookies formulated with soybean flour, chicken liver, and purple sweet potato to improve their nutritional values. Soybeans and chicken liver are rich in iron, whereas purple sweet potatoes are rich in vitamin C. This study employed an experimental method with a completely randomized design. The cookies were prepared at Universitas Negeri Semarang, and their nutritional content was analyzed at Universitas Muhammadiyah Semarang in January–February 2025. Iron, vitamin C, and crude fiber were analyzed using colorimetry, iodometric titration, and enzymatic gravimetry, respectively. Data were analyzed using one-way ANOVA and Duncan's test. The results showed significant differences in the iron, vitamin C, and crude fiber contents among the formulas (F1, F2, F3, and F4) (p = 0.000). The highest values were found in F4, with 12.48 mg/100 g iron, 43.66 mg/100 g vitamin C, and 9.88% crude fiber. In conclusion, F4 has the potential to prevent anemia during pregnancy. With a serving size of 20 g, it can provide 92.4% of the daily iron requirement and 102.7% of the vitamin C requirement per snack portion for pregnant women.